Circular Economy and Blockchain Technology : Pathways to Economic, Social, and Environmental Sustainability - Tewary, Tavishi; Jain, Vranda (Prabandhan: Indian Journal of Management, 2026)
Purpose : The study investigated how blockchain technology (BCT) connects circular economy practices with economic, social, and environmental sustainability, addressing the limited empirical evidence on how digital technologies configure circular initiatives and shape multidimensional sustainability outcomes. Methodology : The proposed model was tested using partial least squares structural equation modeling on survey data collected from 176 respondents across three Indian states. Findings : Circular economy practices were strongly related to the level of BCT adoption and exerted a direct positive influence on economic, social, and environmental sustainability, while blockchain adoption itself positively affected all three sustainability dimensions and partially mediated the relationship between circular practices and sustainability outcomes. Implications : The results underscored the need for complementary digital investments alongside circular economy strategies to realize system-wide and scalable sustainability benefits, offering guidance for practitioners and policymakers pursuing sustainable development. Originality : The study advanced sustainability and digital transformation literature by empirically integrating circular economy practices and BCT into a unified framework that links digitalization with multidimensional sustainability performance.